2018
DOI: 10.4103/aam.aam_52_17
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitude to deceased kidney donation among health-care workers in Sokoto, Nigeria

Abstract: Background:Access to renal replacement therapy by the increasing population of patients with end-stage kidney disease across Sub-Saharan Africa, including Nigeria, has become a major public health challenge. Although deceased kidney donation constitutes a viable source, its uptake by patients is contingent on its acceptance by health-care workers.Objectives:The aim of this study is to assess the awareness and attitude to deceased kidney donation among health-care workers in Sokoto, Nigeria.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Therefore, a solid and transparent procedure is necessary to ensure trust and increase donation rates. Likewise, ample body of evidence 2 , 40 42 confirms a profound influence of attitudes on donors’ WTD. However, few authors have highlighted the need of an effective policy for converting people’s positive attitudes to actual donations.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, a solid and transparent procedure is necessary to ensure trust and increase donation rates. Likewise, ample body of evidence 2 , 40 42 confirms a profound influence of attitudes on donors’ WTD. However, few authors have highlighted the need of an effective policy for converting people’s positive attitudes to actual donations.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Having an organ transplant can be more cost effective than alternative therapies. 2 , 3 However, the current supply of transplantable organs is much lower than the need for them. This widening gap between the number of organ donors and recipients is a serious challenge for governments worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…About 10% of the world population are affected by CKD with a high population of sub Saharan Africans that are mainly young adults between 20-50 years (Gama et al, 2012). CKD is asymptomatic in its early stage thereby causing a delay in early detection and the missing opportunities in preventing the progression of the disease to end stage renal disease (ESRD) that requires renal replacement therapy (Ngwobia et al, 2018). Renal replacement therapy (RRT) which include kidney transplant and dialysis that is available as hemodialysis and peritoneal dialysis are unaffordable or unavailable (Makusidi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, studies conducted in small several hospitals and small scale communities reported a high burden of CKD across the country (Oluyombo et al, 2017). This high burden of ESRD is a result of poor healthcare services, poverty, ignorance, inadequate manpower and infrastructures (Ngwobia et al, 2018). Patients with CKD present a variety of metabolic and nutritional abnormalities (Heimburger et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To explore beliefs of individuals about their ability to donate and test the validity of an organ donation scale ( 13 15 )…”
Section: Introductionmentioning
confidence: 99%